Survey Of Facilities And Infrastructure In The Department Of Youth And Sports Year 2019 District Bangkalan - Heni Yuli Handayani (Performa, 2019)
Provision of learning experiences in Sports Physical and Health Education subjects is not solely from the normative delivery of material by the teacher, but also how students can make good use of the facilities and infrastructure they have to support the learning process and the athlete's training process. The smoothness of Physical and Physical Education learning can be measured one of them from the availability of facilities and infrastructure. Adequate facilities and infrastructure will reflect the quality of learning carried out, so that educational goals will be achieved properly. Conversely, inadequate facilities and infrastructure will have an impact on the low quality of education, even the curriculum cannot run well. The learning process of Physical Education Sports and Health absolutely requires facilities and infrastructure to achieve goals, because it places more emphasis on developing students' motor skills. A facility and infrastructure will be adequate if the quality is efficient and in terms of quantity sufficient to meet the needs of athletes in Bangkalan Regency.